Emotion-Performance Relationships in the Acquisition and Adaptation of a Complex Skill: Are Relationships Dynamic and Dependent on Activation Potential?. Issue 1 (1st January 2021) - Jorgensen, Ashley; Day, Eric Anthony; Huck, Jonathan T.; Westlin, Joseph; Richels, Kelsey; Nguyen, Chris
ABSTRACT: Although the importance of emotions to self-regulation has been noted in the extant literature, little empirical research has examined how fluctuations across a range of emotions are related to performance. Accordingly, this laboratory study of 214 undergraduates (58% male) learning a complex videogame examined the dynamics of within-person emotion–performance relationships during skill acquisition and adaptation. We observed the direction of relationships was consistent with the valence of emotions at both the within- and between-person levels. In addition, we observed dynamic relationships and an interplay between valence and activation potential. Dynamic relationships were observed for negative but not positive emotions. Activation potential made a difference for positive but not negative emotions. Implications for emotion control strategies in complex task learning are discussed.